(untitled) (Bangladesh Journal of Plant Taxonomy, 2021)
Salacia comprises 200 species throughout the tropical countries. In Sri Lanka, five species of this genus S. chinensis, S. diandra, S. oblonga, S. reticulata and S. acuminatissima are recorded that are considered as the synonyms under S. diandra by Wadhwa in 1996 during the revision of genus. These species are very much similar in vegetative morphology and their flowering is irregular and rare. Due to these reasons, their proper identification and determination are difficult and identification of new combinations of taxonomic characters is necessary. A multivariate analysis was conducted for 98 distinct populations using 20 vegetative and 43 leaf anatomical characters including PCA, PCO, CA, SIMPER and correlation analysis. The results support the recognition of four phenetic groups, which corresponds to species S. chinensis, S. reticulata, S. oblonga and S. diandra. S. acuminatissima that was recognized by Kostermans (1992) was not supported by the analysis and formed a cluster together with S. diandra with no support as a separate cluster. The study failed to recognize any distinct vegetative characters to define these taxa but propose a combination of vegetative or leaf anatomical characters and also highlights the necessity of molecular data to supplement the vegetative and leaf anatomical data to resolve the ambiguity between the S. acuminatissima and S. diandra. Bangladesh J. Plant Taxon. 28(2): 429-439, 2021 (December)